Eksploatacja gospodarcza Generalnego Gubernatorstwa przez Rzeszę Niemiecką w latach 1939–1945 - Schwaneberg, Sonja (Pamięć i Sprawiedliwość, 2009)
The article seeks to illuminate the formulation and implementation of Nazi economic policy in the General Government (GG). The GG had initially been envisaged as a reception area for racially undesirable population and as a territory for economic plunder and cheap labour; but these ideas soon proved impossible to implement. In order to establish the GG as an area of low living costs and as a reserve of cheap labour, and to avoid any dependency on food subsidies from the Reich, it was imperative to keep immigration from the incorporated territories within acceptable limits. But for the GG to be able to take in more population, the economy needed to be rationalised. The analyses of the key economic sectors of agriculture, industry and labour show that the structural problem of economic utilisation of the GG was that the Reich authorities were simultaneously pursuing various mutually exclusive exploitation and utilisation projects. At the same time that they demanded increased delivery of agricultural products and Polish labourers, they also aimed to increase industrial and agricultural productivity in the GG and to transfer to the GG industries from territories more vulnerable to air strikes. In addition to these economic contradictions, political factors have to be taken into account, such as the damaging repercussions of resettlement actions and the terror against the population in the GG. Although the Reich’s expectations were never fully met, the Reich still extracted quite a substantial amount of foodstuffs and labour. The Reich authorities blamed the failure to fully meet the Reich’s demands for the delivery of agricultural produce and labourers and the anarchic situation in the industrial sector on Frank’s failure to create an economic order in the GG. However, while it could certainly be argued that a more systematic exploitation would have allowed even more extraction from the GG for the Reich’s purposes, the question remains how a more orderly system of exploitation could have been set up under the existing conditions. The article suggests that the mixture of repression, controls, and pragmatic laissez-faire toleration of the black market accepted by Frank and his GG administrators was more effective than the unrealistic demands for total control of the economy put forward by the Reich ministries.